REFLEKSI KRITIS IDEOLOGI PENDIDIKAN KONSERVATISME DAN LIBRALISME MENUJU PARADIGMA BARU PENDIDIKAN - Wisarja, I Ketut; Sudarsana, I Ketut (LPPM Undiksha, 2017)
The general assumption is that education as a means of acquiring knowledge and knowledge is not indisputable, but the notion that education is available only in the formalist environment is naÃ¯ve, as it excludes other possibilities where education is also derived from non-formal (andragogic) educational models such as; education pasraman, ashram, pesantren, and so forth. Conservative paradigm with all its attributes, such as; educational fundalism, educational intellectualism, and educational conservatism, basically more towards the attainment of a quo-vadis form of education and harmonization, without any criticism of all pre-existing conditions and post-conditions of knowledge and awareness. This concept is basically not too far from the mere establishment view of educational practices (prison education / shackles), which ultimately leads to the assumption / stigma that educational intellectualism can not be separated from the subject of interest. Then comes the libral paradigm with all its attributes that assume the main purpose of education is to preserve and improve the existing social order, by educating based on existing social reality. The culmination is anarchism of education which tends to a form of conception of the idea of how to rationalize education, eventually this paradigm tends to reject firmly existing order and construct into a more humane and moral education.